The conserved active site aspartate residue is required for the function of the chloroplast atypical kinase ABC1K1 - Turquand, Maud; Justo Da Silva, Ana Rita; Pralon, Thibaut; Longoni, Fiamma; Kessler, Felix; Collombat, Joy (Frontiers in Plant Science, 2024)
The Arabidopsis abc1k1/pgr6 (Activity of BC1 complex / proton regulation 6) mutant is characterized by photosynthetic and conditional developmental phenotypes triggered by stressful red as well as high light. The Arabidopsis ABC1K-like kinases belong to the atypical kinase family and contain conserved ATP-binding and hydrolysis motifs, but their physiological requirement has never been investigated. By mutation to asparagine, we demonstrate that the highly conserved active site aspartate residue within ATP-binding motif VIIb is required for the physiological functions of ABC1K1. Complementation of the abc1k1 knock out mutant with ABC1K1 D400N, failed to restore the wildtype phenotype. These results provide in vivo evidence for a critical role of the active site aspartate residue (D400) of ABC1K1.